Anti-TNF Withdrawal in Inflammatory Bowel Disease - Torres,Joana (2016)
The introduction of the anti-tumor necrosis factorÎ± agents (anti-TNFÎ±) in clinical practice has greatly advanced the treatment of inflammatory bowel disease. The use of these medications results in durable remission in a subset of patients, preventing surgery and hospitalizations. However, there are some concerns about safety and costs associated with their long-term use. Therefore, anti-TNF withdrawal has emerged as an important consideration in clinical practice. Herein our goal was to discuss the available evidence about anti-TNFÎ± discontinuation in IBD that could inform the clinician on the expected rates of relapse, the potential predictors of relapse, as well the response to re-treatment.